Uji Daya Hambat Jamur Endofit dan Eksofit dalam Menekan Pertumbuhan Fusarium oxysporum f.sp. vanillae Penyebab Busuk Batang Panili Secara In Vitro - SUNITI, NI WAYAN; SUDARMA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 6 No 2 (2016), 2016)
Study on In Vitro Inhibitory Ability of Endophytic and Exophytic Fungusin Suppressing the Growth of Fusarium oxysporum f.sp. vanillae thatCauses Stem Rot of Vanilla. Vanilla stem rot disease caused by Fusarium oxysporumf.sp. vanillae , is still a very dangerous disease and feared by vanilla farmers. Disease until thepresent time there does not yet appear adequate control strategies for the disease. On the basisof these problems interested studied the use of endophytic fungi and exophytic existing on theleaves and stems of healthy plants , which have potential as a biological agent to controlpathogens . The study was conducted in three stages: (1 ) isolation of the pathogen and fungalendophyte and exophytic, (2) identification of pathogenic microscopic morphology, fungalendophyte and exophytic, and (3) test the inhibition of fungal endophyte and exophyticagainst pathogens. Fungi are found as the leaves are Aspergillus niger and Rhizopus spp., Onexophytic on the trunk is Trichoderma sp . and Fusarium spp., as a leaf endophytic found A.niger and Neurospora spp. and as endophytic rod is Neurospora spp . The highest prevalenceachieved by Neurospora spp . which is equal to 100 % on endophyte stem, while Rhizopusspp., and Fusarium spp. by 90 % respectively, exophytic on the leaves and stems. The testresults found that the inhibition of leaf eksofit Rhisopus spp . give up inhibition ranged from70.37±3.2% - 100% , while A. niger amounted to 72.22% . In exophytic on rod found onlyTrichoderma sp. inhibit pathogens by 73.70±3.57%. In endophytic on leaf found A. niger at70.37±3.2% , while Neorospora spp. ranging from 79.11±3.21% - 88.50±2.10%. In theendophytic on trunk was found Neurosporas spp. amounting to 70.74±3.57% - 79.26±1.28%.
Keywords: Endophytic and exophytic fungi; F. oxysporum f.sp. vanillae; inhibition test and vanilla